A study of pedagogical knowledge and teaching creativity among Arabic language teachers in Malaysia - Mohd Ala-Uddin, Othman; Mohammad Rusdi, Ab Majid; Che Mohd Zaid, Yusof; Kasyfullah, Abdul Kadir; Jumadil, Saputra; Zawawi, Ismail (2021)
Pedagogical knowledge is a unique skill that should be owned by teachers, especially for Arabic language teachers. It is one of the elements in Technological Pedagogical Content Knowledge. This study aims to identify the pedagogical knowledge and teaching creativity of Arabic language teachers in Malaysia. Also, to examine the correlation between pedagogical knowledge and teaching creativities. This quantitative study through survey questionnaire (by self-administered) conducted on 530 Arabic language teachers around Malaysia, including Sabah and Sarawak, participated in this study. The sample selected by using a random sampling technique. The data analysed using descriptive statistics and correlation analyses involving mean, standard deviation and Person correlation assisted by statistical software, namely SPSS-20. This study showed that the Arabic language's pedagogical knowledge and teaching creativity among Malaysia teachers are categorised as high. This study also found a positive and significant correlation between pedagogical knowledge and teaching creativity with the correlation coefficient is 63.1 per cent. Its correlation categorised as moderate. In conclusion, this study has identified that Arabic language teachers in Malaysia have excellent pedagogical and teaching creativity knowledge.